Antimicrobial Stewardship in the Emergency Department: Challenges, Opportunities, and a Call to Action for Pharmacists. (December 2016) - Bishop, Bryan M.
Antimicrobial resistance is a national public health concern. Misuse of antimicrobials for conditions such as upper respiratory infection, urinary tract infections, and cellulitis has led to increased resistance to antimicrobials commonly utilized to treat those infections, such as sulfamethoxazole/trimethoprim and flouroquinolones. The emergency department (ED) is a site where these infections are commonly encountered both in ambulatory patients and in patients requiring admission to a hospital. The ED is uniquely positioned to affect the antimicrobial use and resistance patterns in both ambulatory settings and inpatient settings. However, implementing antimicrobial stewardship programs in the ED is fraught with challenges including diagnostic uncertainty, distractions secondary to patient or clinician turnover, and concerns with patient satisfaction to name just a few. However, this review article highlights successful interventions that have stemmed inappropriate antimicrobial use in the ED setting and warrant further study. This article also proposes other, yet to be validated proposals. Finally, this article serves as a call to action for pharmacists working in antimicrobial stewardship programs and in emergency medicine settings. There needs to be further research on the implementation of these and other interventions to reduce inappropriate antimicrobial use to prevent patient harm and curb the development of antimicrobial resistance.